Penerapan Bimbingan Kelompok dengan Teknik Permainan Untuk Menurunkan Tingkat Kecanduan Media Sosial - Nabilla Ashari Sulistyo; Rosa Imani Khan; Devi Asmindra Milasanty (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Social media addiction is a behavior that always accesses social media while ignoring other activities so that many bad things can be detrimental. The increasing use of gadgets among students to adults indicates that this behavior is rampant. If this continues to increase, communication with other people or the surrounding environment will be directly disrupted. This research procedure uses classroom action research where the stages carried out are 4, namely planning, action, observation, and reflection. The social media addiction instrument used is adopted from the "Social Media Scale Addiction Scale-Student Form (SMAS-SF)" instrument. The results showed a significant difference between the pretest and posttest scores, with students experiencing a decrease in social media addiction from the high category to the medium and low categories. The average score in the pre-cycle was 93, cycle I was 73, and cycle II was 65. So it can be concluded that the implementation of group guidance services with the educational game technique "My Social Media Journey" is effective in reducing the level of social media addiction in class X-6 students of SMAN 3 Kediri.